2016
DOI: 10.1002/ccr3.425
|View full text |Cite
|
Sign up to set email alerts
|

The evolving features of Nicolaides–Baraitser syndrome – a clinical report of a 20‐year follow‐up

Abstract: Key Clinical MessageNicolaides–Baraitser syndrome (NCBRS) is a rare genetic condition associated with SMARCA2 gene mutations. Clinical diagnosis is challenging as its features evolve with time. The 20 years follow‐up of our NCBRS patient, with a previously unreported SMARCA2 mutation, illustrates the syndrome's natural history and its clinical variability, especially in a milder form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Clinically, the NCBRS cases encompassed the variable spectrum of disorder severity (detailed clinical data found in Additional file 2: Table S1). SMARCA2_5 and SMARCA2_11 have been previously published as NBS24 and NBS26 [17], SMARCA2_1 has also been previously described by our group [29]. Unique features noted in the cohort included ophthalmologic abnormalities, such as unilateral retinal detachment in SMARCA2_1, bilateral infantile glaucoma in SMARCA2_4 and myopia in SMARCA2_12 and SMARCA2_14.…”
Section: Research Participantssupporting
confidence: 57%
“…Clinically, the NCBRS cases encompassed the variable spectrum of disorder severity (detailed clinical data found in Additional file 2: Table S1). SMARCA2_5 and SMARCA2_11 have been previously published as NBS24 and NBS26 [17], SMARCA2_1 has also been previously described by our group [29]. Unique features noted in the cohort included ophthalmologic abnormalities, such as unilateral retinal detachment in SMARCA2_1, bilateral infantile glaucoma in SMARCA2_4 and myopia in SMARCA2_12 and SMARCA2_14.…”
Section: Research Participantssupporting
confidence: 57%
“…Among the 70 mutations reported in NCBRS patients, one is an in-frame 6-bp deletion, two are in-frame multi-exon deletions affecting the ATPase domain, and 62 are missense mutations. Of the 62 missense mutations, 60 are mapped to the ATPase domain, one is proximal but outside the ATPase domain, and the other is in the bromo domain (Van Houdt et al, 2012 ; Sousa et al, 2014 ; Ejaz et al, 2016 ). Notably, deletions encompassing human BRM locus have not been found in NCBRS (Christ et al, 1999 ).…”
Section: Role Of Baf Complex In Neurodevelopmental Disordersmentioning
confidence: 99%
“…Because null BRM KO mice do not show major developmental defects (Koga et al, 2009 ; Magnani and Cabot, 2009 ) and none of the identified mutations cause truncated proteins, it has been proposed that the mutations in BRM cause GOF or dominant-negative effects. Hence, these mutations possibly interfere with the ability of ATP hydrolysis by native BRM protein (Van Houdt et al, 2012 ; Ejaz et al, 2016 ). In addition to BRM , missense mutations in BAF47 (p.Arg366Cys) was also reported to present with NCBRS (Wieczorek et al, 2013 ).…”
Section: Role Of Baf Complex In Neurodevelopmental Disordersmentioning
confidence: 99%
“…Patient's mutation in black. Mutations reported first by [Van Houdt et al, ] in green, [Wolff et al, ] in orange, [Sousa and Hennekam, ] in blue, [Bramswig et al, ] in purple, and [Ejaz et al, ] in pink. *Recurrent mutations.…”
Section: Discussionmentioning
confidence: 99%
“…SMARCA2 is located on chromosome 9p24.3 and its longest transcript has 34 exons. Thus far, 62 missense mutations and three in‐frame deletions clustering in the ATPase domains of exons 15–25 of SMARCA2 have been reported in patients with NCBRS [Sousa and Hennekam, ; Bramswig et al, ; Ejaz et al, ] (see Fig. for schematic diagram of SMARCA2 protein and location of mutations).…”
Section: Discussionmentioning
confidence: 99%